Pengaruh Mikroklimat dan Praktik Pengelolaan Perkebunan Kopi Liberika (Coffea liberica L.) terhadap Tingkat Serangan dan Populasi Hama Penggerek Buah Kopi (Hypothenemus hampei Ferr.) di Kabupaten Tanjung Jabung Barat - Hertanti, Septinita; Wilyus, Wilyus; Hayati, Islah (Universitas Batanghari, 2025)
This study aimed to analyze the effects of microclimate and management practices on the infestation level and population of the coffee berry borer (Hypothenemus hampei Ferr.) in Liberica coffee (Coffea liberica L.) plantations in Tanjung Jabung Barat Regency, Jambi Province. Three categories of plantations with different management levels were observed: well-managed, moderately managed, and unmanaged plantations. The analyzed microclimatic variables included canopy temperature, canopy humidity, light intensity, soil temperature, and soil moisture. In addition, plantation characteristics such as plant age, planting distance, pruning, fertilization, and the fresh and dry weight of weeds were examined to assess their relationship with pest infestation dynamics. The results showed that plantation management level had a significant effect on both infestation rate and population density of H. hampei. Well-managed plantations exhibited the lowest average infestation rate (10.92%), classified as light infestation, whereas unmanaged plantations had the highest rate (29.97%), categorized as moderate infestation. Similarly, the highest pest population was found in unmanaged plantations, with an average of 0.89 individuals per berry. Regression analysis revealed that canopy temperature was the only microclimatic variable significantly affecting H. hampei infestation (p < 0.05). Moreover, both fresh and dry weed biomass showed a significant positive correlation with pest population, indicating that unmanaged weeds may increase micro-humidity favorable for pest development. This study concludes that good plantation management—particularly pruning, weed control, and fertilization—can significantly reduce the population and infestation levels of H. hampei. These findings are expected to serve as a scientific basis for recommending more effective and sustainable pest management strategies in Liberica coffee plantations.